Osteosyntéza pakloubu navikulární kosti Herbertovým sroubem - vlastní modifikace s pouzitím trikortikálního stepu - Kubes, R; Frühaufová, V (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 1999)
Authors in their a short report are presenting possibility of scaphoid reconstruction for nonunion with a modeled tricortical corticocancellous bone graft from the illiac crest after resection of pseudoarthrosis back to the healthy bone in their's own modification. This operation with the possibility of stable osteosyntesis with the use of Herbert screw gives ideal opportunity for restoration of full length and thus also function of navicular bone without use of any postoperative immobilization. Also detailed operation technique is described including a bone graft harvesting and its final modelation. Finally authors are presenting a case of 5 years old pseudoarthrosis of navicular bone in 20 years old women successfully treated by this technique. Key words: pseudoarthrosis of the navicular bone, Herbert screw, tricortical corticocancellous bone graft.